Lecturer at Department of Economics Faculty of Administration, Economics and Information Systems Misr University for Science and Technology Arab Republic of Egypt - Mostafa, Eman (The Arab Journal of Administration, 2021)
Egypt has been facing a structural public budget deficit, as the public revenues are insufficient to cover its public expenditures. At the same time, Egypt’s national economy is showing a steady current account deficit about the balance of payments. Hence, the problem of this research is to analyses the reciprocal relationship between the public budget deficit and current account in Egypt. Deduction and extrapolation are the methodologies employed in this study. A standard model was designed to answer about the research questions which the research builds. The research is divided into four main parts, the first of which handles the theoretical framework and applied studies conducted into the double deficit. The second part of the research is about analysing the relationships between the public budget deficit, the current account deficit, the interest rate of lending and real exchange rate during the period under study. As for the third part, it deals with the standard model used in analysing the phenomenon of double deficit in Egypt. The fourth part deals with the most important conclusions and recommendations of this research. One of the results reached in this research is that it has not been proven yet that there is double deficit in Egypt, but there is that phenomenon of Twin Divergence. The Ricardian equivalence, which assumes that there is no relationship between public budget deficit and current account deficit, has also been rejected. The study has come up with a number of recommendations, the most important of which are: the necessity of both financing the public budget deficit through internal or external borrowing and determining the point at which the state cannot turn to domestic borrowing so that the public debt does not worsen and the interest rates do not rise.